Exploring the effectiveness of e-portfolios in a first-year undergraduate Project Management course - Grasia Chisango (SOTL in the South)
This study explored the effectiveness of e-portfolios as pedagogies in teaching and learning for undergraduate Project Management students at a rural university in the Eastern Cape Province, South Africa. The outbreak of COVID-19 resulted in institutions of teaching and learning adopting digital tools to teach and assess students. For some lecturers, it was their first time using digital tools in their classroom practices, and the tools’ effectiveness was unknown. Therefore, this study explored the effectiveness of e-portfolios as pedagogical devices in the teaching and learning of undergraduate Project Management students. Social constructivism and community of inquiry (CoI) frameworks guided the study. In this study, qualitative data was collected from an undergraduate class with a cohort of 35 students. Data was collected through focus group discussions and a semi-structured interview was used. The collected data was analysed using the thematic approach. Ethical considerations were adhered to. The findings revealed that using e-portfolios as pedagogical devices resulted in the development of 21st-century skills, such as communication, collaboration, and creativity, through conversations and social interactions. This study highlights the importance of equipping students with digital skills before designing e-portfolios. Challenges associated with the use of e-portfolios include poor internet connection and load-shedding.